Otolith elemental characteristics of whitefish (Coregonus lavaretus) from brackish waters of the Gulf of Bothnia, Baltic Sea. Issue 1 (5th October 2015) - Hägerstrand, Henry; Himberg, Mikael; Jokikokko, Erkki; von Numers, Mikael; Mrówczyńska, Lucyna; Vasemägi, Anti; Wiklund, Tom; Lill, Jan‐Olof
Abstract: To investigate whether European whitefish ( Coregonus lavaretus ) groups in the brackish (≤7%) Gulf of Bothnia (Baltic Sea) express specific otolith elemental characteristics, concentrations of elements (Ca, Ba, Sr, Zn, Mn, Fe) in whole otoliths were studied by inductively coupled plasma‐optical emission spectrometry. Whitefish ( N = 67) were sampled from six different latitudinal sites; four in the sea and two in rivers along the west coast of Finland, and from a fresh water lake for comparison. The concentration of several elements showed significant differences among sampling sites. Otolith Ba concentrations were higher at the northern sampling sites compared to the southern ones, thereby showing negative association to capture‐habitat salinity. In contrast, otolith Sr and Zn concentrations were lower at the northern sampling sites, thereby associating positively to capture‐habitat salinity. Otolith Mn concentrations did not associate with latitude or salinity but markedly varied between sampling sites. Elevated Fe concentrations occurred in fish otoliths from the two northernmost sites. Ca concentrations were at the same levels in otoliths from all whitefish samples. Otoliths of whitefish from the lake had very high Ba and low Sr concentrations compared to concentrations in otoliths from whitefish in the sea and rivers. Our results show that otolith elemental characteristics of whitefish vary considerably at various geographic scales showing high potential for population identification using elemental fingerprints. Analysis of otolith elemental characteristics may therefore provide an efficient tool for the identification of main areas of residence, spawning locations, and migration routes, thus contributing towards the sustainable management of whitefish stocks.